PENINGKATAN KOMPETENSI GURU BK DALAM PENYUSUNAN PROGRAM BK MELALUI QUALITY CONTROL CIRCLE DI SMPN 2 YOGYAKARTA - , Suliyah ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This study is aimed to determine how to improve BKâs teachersâ competence in the preparation of the program through the Quality Control Circle and to know the magnitude of the increase of the teacherâs competence in the program, before and after it had been done the Quality Control Circle in SMP N 2 Yogyakarta. This study is an action research study. This is also a descriptive study because the research illustrates the attempts which were done through the Quality Control Circle. How the force control is applied and how the results can be achieved. The implementation is done using two cycles, in which the cycles are an ongoing series of interrelated. In the first cycle, the administration and BKâs organization of teachersâ personal work previously in the indicators of monthly work program, weekly work program, the daily work program, the service unit, the list of foster care students and additional administrative data. These indicators have increased significantly after the actions had been done using The Quality Control Circle. The impact of services to students have not shown an increased in the quality of cycle I. cycle 2 conducted the repairs on the accuracy of the BK service program and then doing the BK classical service continuously. The measurement results of students impact on the second cycle shows significant improvement in BKâs teachers service quality and competence.